Inland and foreign Erwinia amylovora isolates by carbohydrate utilization - Végh, Anita; Hevesi, Mária; Palkovics, László (Acta Agraria Debreceniensis, 2010)
Fire blight, a plant disease caused by the bacterium Erwinia amylovora, produces serious losses in apple and pear orchards all over the world. Since the appearance of fire blight in Hungary (Hevesi, 1996) Erwinia amylovora isolates were collected in different years, from different hosts and areas in order to establish gene bank for future epidemiological studies. We had isolates from foreign countries as well. The aim of our research was to compare all of the Hungarian and foreign isolates by carbohydrate utilization. In our experiments effect of carbohydrates on E. amylovora multiplication was determined using API 50 CH strip (bioMérieux, France). By the API 50 CH strip method we checked a number of unstudied carbohydrates. The results of the tests shows colour changes. Based on utilization of 49 carbohydrates of API 50 CH kit by E. amylovora isolates, two groups of carbohydrates can be defined: “Utilized” - and “Not utilized” carbohydrates. All isolates utilized 20 different carbohydrates after 164 hour incubation. Conversely, isolates also could be divided into four groups (1, 2, 3, 4) by arbutin and raffinose utilization. In group 1.-isolates utilize arbutin; 2.- utilize raffinose; 3.- utilize both arbutin and raffinose; 4. -utilize neither arbutin nor raffinose. Presumably carbohydrate content of nectar could play an important role on invasion of the (E. amylovora) bacterium via flower. It could be concluded that the carbohydrate utilization – completed with genetic analysis – can be used for characterization of Erwinia amylovora isolates.